Highly sensitive label-free antibody detection using a long period fibre grating sensor - Liu, LiangLiang; Marques, Leonel; Correia, Ricardo; Morgan, Stephen P.; Lee, Seung-Woo; Tighe, Patrick J.; Fairclough, Lucy C.; Korposh, Sergiy (Elsevier, 2018)
An optical fibre long period grating (LPG) biosensor is appealing in the detection of biomolecules because of the high sensitivity, label-free and real-time measurement. The miniaturized size, ability of remote sensing and immunity to electromagnetic interference of the LPG biosensor provide various possibility of single-point sensing in situations such as point of care diagnostics and in vivo measurement. Two optical fibre LPG based biosensors are reported for detection of streptavidin (SV) and immunoglobulin M (IgM) respectively. The LPG is coated with a film containing three layers of Poly(allylamine hydrochloride)/gold coated silica nanoparticles via the layer-by-layer method. Biotin is covalently bonded to the surface of the gold shell by means of the formation of an amide bonds for detection of streptavidin. The concentration of SV in water for detection varied from 1.25 nM to 2.7 μM. The LPG sensor, operating close to the phase matching condition shows a high sensitivity of 3.88 (ng/mm2)−1 and a detection limit of 0.86 pg/mm2 for the detection of SV. The limit of detection is 22 times lower than previously demonstrated with this type of sensor. The developed IgM sensor has the same configuration of film but has anti-IgM embedded on the LPG instead of biotin, demonstrating versatility of the sensing platform. This was used for the detection of human IgM with concentrations from 15.6 μg/ml to 1 mg/ml. The LPG sensor exhibits a sensitivity of 11 nm (ng/mm2)−1 for the detection of IgM with a detection limit of 15 pg/mm2. The developed highly sensitive IgM sensor shows the potential application of clinical point of care for detection of lower concentration of IgM in vitro. The proposed biosensor exhibits high sensitivity and rapid detection of low concentrations biomolecules from the small size of SV to the large size of IgM.